PENGGUNAAN ZEOLITE SINTETIS DALAM PENGERINGAN GABAH DENGAN PROSES FLUIDISASI INDIRECT CONTACT - Affian Widjanarko; R Ridwan; M. Djaeni; R Ratnawati (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro, 2013)
Grain drying process being one of the constraints experienced by grain farmers in Indonesia. This is because the farmers still rely on the sun to dry their grain crops. Meanwhile, the drying is still constrained by the type of season. Drying by fluidization processes using zeolite considered an alternative to grain drying process. The purpose of this research, make use of zeolite to accelerate the drying of grain, determine the relation of drying air temperature with drying rate and determine the relation of air flow rate into the dryer with drying rate. The operating conditions in this experiment is the drying air temperature 30oC; 40°C; 50oC and 60oC), drying air flow rate (1 m/s; 1,5 m/s; 2 m/s and 2,5 m/s) and 1 kg of zeolite. The research was conducted by flowing dry air at a specific operating conditions and then contacted with the grain in the fluidized bed to obtain the water content of 12-14%. The results obtained indicate the temperature of 30oC, Nc = 0,0082, while the temperature of 60°C, Nc = 0,0138. In the air flow rate of 1 m/s, Nc = 0,0094 while the air flow rate of 2,5 m/s, Nc = 0,0118. From this data it can be concludedthatthe higher the temperature and the rate of the air dryer, the drying rate will be faster, so as to make the drying process faster.